Symposium 3: Networked Learning - a social practice perspective - Jones, Chris (Proceedings of the International Conference on Networked Learning, 2008)
This paper proposes a social practice perspective on networked learning. Networked learning doesn't privilege any particular view of learning and the paper does not claim any special status for a social practice view but it sets out a clear agenda and demarcation for this area of study. The suggestion is that social practice can provide a theoretical lens that allows researchers to examine networked learning in ways that other perspectives do not and that a social practice approach is especially appropriate for research focused on the kinds of changes that are taking place around what has been termed Web 2.0. The term social practice has been developed in relation to commonly used meanings of practice and other available alternatives in academic discourse. It is suggested that social practice should not be viewed as an exclusive or singular perspective. Instead it is suggested that social practice is particularly suitable for examining certain levels of activity in relation to learning and networked learning specifically. Social practice offers a materialist account that places an emphasis on externalities and artefacts rather than processes of learning that take place within the 'head' either as brain functions or as cognitive processes of the mind. This materialist emphasis also stands in contrast to some cultural accounts of practice that emphasise discourse at the expense of other factors. In order to illustrate the kinds of issues that a social practice perspective can assist in researching an account is provided of those aspects that make networked learning a distinct research area. This is then focused on two issues in particular, the place of artefacts in learning and the role of affordances. It can be argued that artefacts have always played a role in learning related to the externalisation of information. In early periods of human development memory and the oral tradition dominated learning and the practices that supported learning. An ability to memorise exactly what was handed on was a key element in preserving and disseminating knowledge and tradition. In later periods the written language provided a repository of knowledge in texts and knowledge and learning were related to the specialist skills of reading, writing, mathematics and arithmetic. Learning still retained a large component of memorisation and repetition as the means to store and reproduce texts were extremely limited. In the modern era with the advent of print technologies texts could be produced and reproduced with much greater ease and reading and writing skills were spread more widely in society. Increasingly memorisation became less important and the ability to understand and deploy conceptual knowledge became more central. This material account of learning as a history of the relationship between social knowing and the technological means available to support social practices provides a backdrop to the central argument of this paper. Networked technologies provide a new set of possibilities that can affect the forms of practice that support knowing and learning. These technologies shift traditional conceptions of time and place and make available large quantities of traditional texts alongside new forms of reification that preserve what has previously been peripheral and ephemeral. Digital technologies shift the boundary between externalising information and externalising cognitive processes. Increasingly those processing and conceptual skills once important to education and learning are delegated to machines and services supplied over the network. The current phase of development captured by the phrase Web 2.0 arguably reasserts the primacy of process over content in that what is externalised is a part of a process that relies on engagement and participation to add value in the system. That is the value for learning does not lie in the technology, nor in content supplied by a central service, rather it lies in the emergent properties arising through the aggregation of many parts in which the whole becomes greater than the sum of its parts.